The Repository Chemotion: Infrastructure for Sustainable Research in Chemistry - Tremouilhac, Pierre; Lin, Chia‐Lin; Huang, Pei‐Chi; Huang, Yu‐Chieh; Nguyen, An; Jung, Nicole; Bach, Felix; Ulrich, Robert; Neumair, Bernhard; Streit, Achim; Bräse, Stefan (Angewandte Chemie International Edition, 2020)
The repository Chemotion provides solutions for current challenges to store research data in a feasible manner. A main advantage of Chemotion is the comprehensive functionality, offering options to collect, prepare, and reuse data with discipline‐specific methods and data‐processing tools.